2017
DOI: 10.1016/j.jbo.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and risk factors analysis of lung metastasis from benign giant cell tumor of bone

Abstract: Pulmonary metastasis of benign giant cell tumor of bone is very rare, and its biological behavior is difficult to predict. In the present study, we analyzed the clinical characteristics of and related risk factors for pulmonary metastasis from this tumor. Forty-six patients with lung metastasis were analyzed. In total, 60.9% of the primary tumors were located around the knee joint. The Campanacci stage of all tumors was stage 3. Surgery of the primary tumor included curettage in 37 patients, resection in 8, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 21 publications
0
55
1
3
Order By: Relevance
“…Based on the Campanacci classi cation, which has been widely accepted for evaluating giant cell tumours, grade III tumours are the aggressive type. A series of studies reported Campanacci grade III as a risk factor for tumour recurrence [20,21] and lung metastasis [22,23]. Recurrence was also reported to be a risk factor for metastasis [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the Campanacci classi cation, which has been widely accepted for evaluating giant cell tumours, grade III tumours are the aggressive type. A series of studies reported Campanacci grade III as a risk factor for tumour recurrence [20,21] and lung metastasis [22,23]. Recurrence was also reported to be a risk factor for metastasis [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies reported Campanacci grade III as a risk factor for tumour recurrence [20,21] and lung metastasis [22,23]. Recurrence was also reported to be a risk factor for metastasis [22,23]. Therefore, T stage and/or Campanacci classi cation played an important role in evaluating the survival of patients with giant cell tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the Campanacci classification, which has been widely accepted in evaluating giant cell tumor, grade III represented the aggressive type. A series of studies reported Campanacci grade III as the risk factor for tumor recurrence [19,20] and lung metastasis [21,22]. The recurrence was also reported to be a risk factor for resulting in metastasis [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…2A). Although classified as a benign tumor, GCTB can be associated with potentially aggressive behavior and a 1-9% incidence of lung metastasis [9]. A Transwell assay indicated that rhCCL20 dramatically promoted GCTSC migration (Fig.…”
Section: Ccl20 Promotes Gctsc Proliferation and Migration In An Autocmentioning
confidence: 98%
“…GCTB is classified as a benign but local aggressive tumor with a 1-9% incidence of lung metastasis [9]. Currently, the most effective treatment for GCTB is surgical excision.…”
Section: Introductionmentioning
confidence: 99%